2009
DOI: 10.1093/humrep/den500
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenous spectrum of CFTR gene mutations in Indian patients with congenital absence of vas deferens

Abstract: This study confirms the molecular heterogeneity of CFTR mutations in CAVD. Although the mutation detection rate is indeed lower in Indian CAVD patients, 74% of the patients tested had at least one CFTR mutation. CAVD alleles with no mutations suggest that other changes may be located at the non-screened sites that require extensive search by direct sequencing. Furthermore, the novel CFTR mutations identified require functional studies in a cell-based system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 41 publications
4
20
0
Order By: Relevance
“…In our study it is documented delta F508 as the most common CFTR gene mutation in Indian population [12,25]. This observation supports the hypothesis that immigration patterns between US, Europe and the Indian subcontinent are contributing to the evolution of CF in the Indian subcontinent.…”
Section: Frequency Of Delta F508 Mutation In Indian Cf Populationsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study it is documented delta F508 as the most common CFTR gene mutation in Indian population [12,25]. This observation supports the hypothesis that immigration patterns between US, Europe and the Indian subcontinent are contributing to the evolution of CF in the Indian subcontinent.…”
Section: Frequency Of Delta F508 Mutation In Indian Cf Populationsupporting
confidence: 89%
“…At PGIMER Chandigarh 100 cases of classical CF were diagnosed by us according to clinical criteria sweat testing and molecular diagnosis over the last 7 years out of which 50 were adult CF infertile males [12]. The incidence in migrant Indian population in USA has been estimated to be 1 in 40,000 [4] and in the UK between 1 in 10,000 to 12,000 [13].…”
Section: Prevalence and Clinical Manifestations Of Cf Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Strong linkage disequilibrium is evident among c.1210‐12T [5] and the Val allele of M470V polymorphism in CBAVD but not in general population (de Meeus et al., ). Studies in population from North India reported 25‐56% frequency of IVS‐9‐ c.1210‐12T [5] (Sachdeva, Saxena, Majumdar, Chadha, & Verma, ; Sharma, Singh, Kaur, Thapa, & Prasad, ; Sharma, Acharyam, et al., ). The ethnicity of the Indian population is quite heterogeneous with different geographical distribution.…”
Section: Introductionmentioning
confidence: 99%
“…All patients with CAVD desiring to have children should undergo CFTR mutation testing, understanding that there are more uncommon mutations not covered by routine testing and novel mutations continue to be discovered (Mak et al 1999;Sharma et al 2009). CBAVD and CUAVD caused by a CFTR gene mutation are phenotypically identical to those unassociated with a CFTR gene mutation (McCallum et al 2001;Radpour et al 2008).…”
Section: Diagnosismentioning
confidence: 99%